The Economic Crisis in Greece and Cyprus. A Comparative Study - Maris, Georgios; Maloina, Stamatia (HAPSc Policy Briefs Series, 2021)
This article presents and compares economic data of Greece and Cyprus during the last decade. An analysis and evaluation is made not only of the economic negotiations but also of the financial statements that took place and affected the national economies of the two countries. The main conclusion of this study is that the economic crisis that hit the two countries during decade has different causes but similar effects in key political and economic sectors of each country.